Association between environmental gradient of anthropization and phenotypic plasticity in two species of triatomines - Fiad, Federico Gastón (2024)
Triatoma garciabesi and T. guasayana are considered secondary vectors of Trypanosoma cruzi and frequently invade rural houses in central Argentina. Wing and head structures determine the ability of triatomines to disperse. Environmental changes exert selective pressures on populations of both species, promoting changes in these structures that could have consequences for flight dispersal. The aim of this study was to investigate the relationship between a gradient of anthropization and phenotypic plasticity in flight-related traits. The research was carried out in Cruz del Eje and Ischilín departments (Córdoba, Argentina) and included 423 individuals of the two species of triatomines. To measure the degree of anthropization, a thematic map was constructed using supervised classification, from which seven landscapes were selected, and nine landscape metrics were extracted and used in a hierarchical analysis. To determine the flight capacity and the invasion of dwellings at different levels of anthropization for both species, entomological indices were calculated. Digital images of the body, head and wings were used to measure linear and geometric morphometric variables related to flight dispersion. One-way ANOVA and canonical variate analysis (CVA) were used to analyze differences in size and shape between levels of anthropization. Procrustes variance of shape was calculated to analyze differences in phenotypic variation in heads and wings. Hierarchical analysis was used to classify the landscapes into three levels of anthropization: high, intermediate and low. The dispersal index for both species yielded similar results across the anthropization gradient. However, in less anthropized landscapes, the density index was higher for T. garciabesi. Additionally, in highly anthropized landscapes, females and males of both species exhibited reduced numbers. Regarding phenotypic changes, the size of body, head and wings of T. garciabesi captured in the most anthropized landscapes was greater than for those captured in less anthropized landscapes. No differences in body size were observed in T. guasayana collected in the different landscapes. However, males from highly anthropized landscapes had smaller heads and wings than those captured in less anthropized landscapes. Both wing and head shapes varied between less and more anthropogenic environments in both species. Results of the study indicate that the flight-dispersal characteristics of T. garciabesi and T. guasayana changed in response to varying degrees of anthropization.